Implementasi Model Problem Based Learning (PBL) dalam Pembelajaran Pendidikan Agama Islam Bagi Santri Inklusif - Irmas Devi Seviana; Afiful Ikhwan; Devid Dwi Erwahyudin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to describe the implementation of the Problem-Based Learning (PBL) model in Islamic Religious Education (IRE) instruction for inclusive students in a pesantren educational setting. The background of this study is based on the need for adaptive and responsive learning that accommodates the diversity of students’ abilities, including those with special needs, who require a more participatory and contextual learning approach. The research method used is a qualitative approach with data collection techniques through observation, interviews, and documentation of the PBL-based PAI learning process. The results indicate that the application of the PBL model enhances students’ active engagement in the learning process, fosters critical thinking skills, and deepens their understanding of religious concepts. Additionally, this model provides space for students with special needs to learn according to their individual abilities and learning styles through group work and the resolution of real-world problems relevant to daily life. Challenges identified include limited learning resources and the need for intensive support for certain students. Nevertheless, overall, the implementation of PBL in Islamic Religious Education (IRE) has proven effective in creating inclusive, interactive, and meaningful learning. Thus, the Problem-Based Learning model can serve as a relevant alternative learning strategy to support inclusive Islamic religious education within the pesantren environment.